Pengaruh Harga Rata-Rata Minyak Mentah Dunia terhadap Penawaran Barang Konsumsi di Indonesia - Handayani, Utami; Ruslan, Dede; Paidi, Paidi (Jurusan Ilmu Ekonomi dan Studi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Lambung, 2025)
Fluctuations in world crude oil prices significantly impact oil-importing countries like Indonesia. These fluctuations affect multiple sectors, including the import of consumer goods, which is vital for the domestic economy. In Indonesia, consumer goods are crucial for economic stability. Thus, understanding how oil price fluctuations influence imports is essential for policymaking. This study investigates the relationship between world crude oil price fluctuations and the import value of consumer goods in Indonesia over an extended period. A quantitative approach was used, treating world crude oil prices as the independent variable and the import value of consumer goods as the dependent variable. Linear regression analysis, supported by descriptive statistical methods, was employed to assess this relationship. The results indicate that world crude oil prices have a significant effect on the import value of consumer goods, with data showing near-normal distribution and low skewness and kurtosis, validating the model. However, positive autocorrelation in the residuals suggests the need for further analysis to ensure the reliability of the model. These findings offer important insights for policymakers on managing the economic impact of oil price volatility on Indonesia’s domestic market. Future research could explore additional factors, such as inflation or trade policy, that may influence this relationship, contributing to more effective economic strategies.